Peran Sistem Informasi dan Pemasaran Digital terhadap Keputusan Pembelian pada Marketplace Tokopedia - Dedy Tri Cahyono; Jaja Miharja; Mujito Mujito; Andri Catur Trissetianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of information systems and digital marketing on Tokopedia's consumer purchasing decisions. The background of this research is based on the increasing use of e-commerce platforms in Indonesia, especially Tokopedia, which demands the optimization of information systems and digital marketing strategies to drive purchase decisions. The method used is a quantitative approach with an accidental sampling technique of 100 Tokopedia user respondents. Data collection was carried out through an online questionnaire, and data analysis used multiple linear regression to test the partial and simultaneous influence of the two independent variables on the dependent variables. The results of the study show that both information systems and digital marketing have a positive and significant influence on purchasing decisions, both partially and simultaneously. Information systems are proven to be the dominant variable with the highest regression coefficient values, showing their important role in shaping user perception and comfort when transacting. Simultaneously, both variables contributed 83.8% to the purchase decision, while the rest were influenced by other factors outside the scope of the study. These findings affirm the importance of strengthening information systems and digital marketing strategies in increasing the effectiveness of e-commerce platforms and encouraging consumer purchasing behavior.